Production process of high-performance permanent magnetic ferrite

By controlling the heating rate and adjusting the insulation time during the sintering heating stage, the problem of low squareness of high-performance permanent magnet ferrite is solved, and the high performance and high squareness are achieved, which significantly improves the anti-demagnetization ability.

CN119822803AActive Publication Date: 2025-04-15ANHUI SINOMAG TECH
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411994168.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-15
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The high-performance permanent magnet ferrite produced in the prior art has a low squareness and cannot have both high performance and high squareness.

Method used

By controlling the temperature increase rate of the sintering heating stage to 1.5-3℃/min, and adjusting the temperature increase rate and insulation time according to the addition proportion of different elements, the uniform diffusion reaction of doped elements in the green body is achieved, and the squareness of ferrite is improved.

Benefits of technology

While ensuring the magnetic properties of high-performance permanent magnet ferrite, the squareness is improved. The squareness of the prepared sintered body exceeds 0.92, significantly improving the anti-demagnetization ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822803A_ABST
    Figure CN119822803A_ABST
Patent Text Reader

Abstract

The invention discloses a production process of a high-performance permanent magnetic ferrite, and belongs to the technical field of preparation of permanent magnetic ferrites. The preparation method comprises the following steps: preparing the following raw materials in parts by weight: 80-88 parts of iron oxide, 0.5-5 parts of strontium carbonate, 3-10 parts of calcium carbonate, 4-10 parts of lanthanum oxide and 1-3 parts of cobalt sesquioxide, and carrying out mixing, pre-sintering, primary grinding, secondary ball milling, magnetic field forming and sintering to obtain a sintered body. In the sintering process, the heating rate within the temperature range of 900 DEG C to 1200 DEG C is strictly controlled to be 1.5 DEG C / min to 3 DEG C / min, the uniform diffusion reaction of doped elements in a green body is guaranteed, the heating rate and the heat preservation time are adjusted at the same time according to the adding proportion of different elements in the high-performance permanent magnetic ferrite, the granularity uniformity of grains in the ferrite is improved, and the high-performance permanent magnetic ferrite is obtained. The squareness is improved, and the demagnetization resistance of the high-performance permanent magnetic ferrite is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of permanent ferrite preparation, and in particular relates to a production process of high-performance permanent ferrite. Background Art

[0002] Ferrite is a kind of metal oxide with ferromagnetism, which is sintered by ferric oxide and one or more other metal oxides (such as nickel oxide, zinc oxide, manganese oxide, magnesium oxide, barium oxide, strontium oxide, etc.). The resistivity of ferrite is much greater than that of metal and alloy magnetic materials, and it also has higher dielectric properties. The magnetic properties of ferrite have higher magnetic permeability at high frequencies, so ferrite has become a widely used non-metallic magnetic material in the field of high-frequency weak electricity.

[0003] At present, most of the research on the performance of permanent ferrites focuses on remanence, intrinsic coercive force and magnetic energy product, while less research has been done on squareness. Squareness will affect the quality of permanent ferrite products and represents the product's ability to resist demagnetization. The better the squareness, the closer it is to 1, the better the anti-demagnetization ability; poor squareness means easy demagnetization.

[0004] The patent application document with publication number CN114956801B discloses a high-squareness permanent strontium ferrite magnetic material and its preparation method, which adopts segmented temperature setting during sintering, adopts different heating rates in the initial stage of sintering, the middle stage of sintering, and the high-temperature sintering stage, controls the grain morphology and diameter / thickness ratio, and makes the sample have good comprehensive performance. However, although the permanent strontium ferrite magnetic material prepared in the embodiment of the technical solution has a high squareness, its intrinsic coercive force is only 2500-3000Oe, and after adjusting the raw material input method in the comparative example, even under the same sintering conditions, the squareness of the high-performance permanent strontium ferrite magnetic material is also low, and it cannot have both high performance and high squareness, and the prepared material has defects. Summary of the invention

[0005] The purpose of the present invention is to provide a production process for high-performance permanent ferrite to solve the problem of poor squareness of high-performance permanent ferrite produced by the prior art.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] The present invention provides a production process for high-performance permanent ferrite, comprising the following steps:

[0008] Step 1, prepare raw materials according to weight proportions, iron oxide: 80-88 parts, strontium carbonate: 0.5-5 parts, calcium carbonate: 3-10 parts, lanthanum oxide: 4-10 parts, cobalt trioxide: 1-3 parts, and mix the raw materials evenly to obtain a mixture;

[0009] Step 2: adding water to the mixture to obtain a primary slurry, drying the primary slurry, pre-sintering the primary slurry to obtain a primary pre-burned material, and grinding the primary slurry to obtain a primary pre-burned material powder;

[0010] Step 3, adding composite auxiliary materials and water to the primary pre-burned powder for secondary ball milling to obtain secondary slurry;

[0011] Step 4: The secondary slurry is subjected to magnetic field molding to obtain a green body, and the green body is placed in a sintering kiln. After heating to 900°C, the temperature is increased to 1200°C at a heating rate of 1.5-3°C / min, and kept warm for 60-120 minutes to obtain a sintered body, and the squareness of the sintered body is greater than 0.92.

[0012] Furthermore, the purity of the iron oxide is greater than 99.0%, the purity of the strontium carbonate is greater than 98.5%, the purity of the calcium carbonate is greater than 98.5%, the purity of the lanthanum oxide is greater than 99%, and the mass fraction of cobalt in the cobalt trioxide is greater than 72%. Controlling the purity of the raw materials can reduce the introduction of impurity elements and avoid affecting the performance of the ferrite.

[0013] Furthermore, in step 2, the pre-sintering temperature is 1250-1350° C. and the holding time is 0.5-4 hours. Pre-sintering can promote the solid phase reaction between the raw materials, generate part of the ferrite phase, reduce the sintering shrinkage of the finished product and improve the completeness of the reaction.

[0014] Furthermore, in step 2, the first grinding device is a Raymond mill, and the particle size of the first pre-sintered material powder is 1.5-3 μm. The first grinding refines the pre-sintered material so that the subsequent addition of composite auxiliary materials is more uniform.

[0015] Further, in step 3, the mass ratio of the secondary ball milling is as follows:

[0016] Ingredients: ball: water = 1: (5-15): (1-3).

[0017] Secondary ball milling can further refine the particles, increase the contact area between ions, promote the solid phase reaction, and improve the densification and grain growth of the product.

[0018] Furthermore, calculated by the percentage of the mass of the primary pre-burned powder, the composite auxiliary materials include:

[0019] CaCO3: 0.1-1%, SiO2: 0.05-0.4%, dispersant: 0.1-0.5%, borate: 0.1-0.5%.

[0020] The composite auxiliary materials have the functions of promoting densification growth, reducing losses and improving dispersion in the ferrite preparation process, which together improve the magnetic properties and frequency characteristics of the ferrite material.

[0021] Furthermore, the dispersant is at least one of calcium gluconate and sorbitol.

[0022] Furthermore, the borate is calcium borate.

[0023] Furthermore, the particle size of the secondary slurry is 0.6-1.0 μm.

[0024] Furthermore, in step 4, the magnetic field strength of the magnetic field forming is 800-1000 kA / m; the density of the green body is 3.3-3.45 g / cm 3 , the green density will affect the densification process of sintering.

[0025] Beneficial effects of the present invention:

[0026] (1) Since high-performance permanent ferrites need to be doped with metal ions and rare earth elements, and the diffusion reaction of metal ions and rare earth elements in the material mainly occurs in the high-temperature heating stage, the present invention controls the heating rate of the sintering heating stage (900-1200°C) to 1.5-3°C / min, so as to achieve uniform diffusion reaction of the doped elements in the green body, avoid partial concentration leading to uneven particle size in the sintered body, thereby ensuring the magnetic properties of the high-performance permanent ferrite and improving the squareness. In the entire production process, only the heating rate of the high-temperature heating stage needs to be controlled, and the process is simple.

[0027] (2) In the production process provided by the present invention, the heating rate and the holding time (900-1200°C temperature range) are adjusted simultaneously according to the addition ratio of different elements in the high-performance permanent magnet ferrite, so as to improve the uniformity of the grain size of the ferrite and improve the squareness. Lanthanum, as a rare earth element, will replace trivalent iron ions into the lattice due to its large ionic radius, and the solubility of lanthanum ions is limited, and a secondary phase LaFeO3 will be formed. The secondary phase gathers at the grain boundary and affects the diffusion reaction of other ions, so that the uniformity of the grain size of the ferrite is reduced. When the proportion of lanthanum is high, the heating rate needs to be increased to promote the rapid diffusion of lanthanum ions, shorten the holding time, and avoid the precipitation of lanthanum during the reaction process, thereby reducing the secondary phase and uniformly diffusing the reaction; the cobalt element has a smaller ionic radius than lanthanum, and diffusion is easier. Its embedding will cause changes in the stress distribution in the lattice, thereby hindering the normal growth of grains and promoting grain refinement. It is necessary to reduce the heating rate and extend the holding time to achieve sufficient diffusion reaction and inhibit grain growth. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The present invention will be further described below in conjunction with the accompanying drawings.

[0029] Figure 1 is a demagnetization curve of the sintered body prepared in Example 1 of the present invention;

[0030] Figure 2is an electron microscope image of a sintered body prepared in Example 1 of the present invention;

[0031] Figure 3 It is an electron microscope image of the sintered body prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] Step 1: prepare raw materials according to weight proportions: 85 parts of iron oxide, 1 part of strontium carbonate, 5 parts of calcium carbonate, 5 parts of lanthanum oxide, and 2 parts of cobalt trioxide. Mix the raw materials evenly to obtain a mixture.

[0035] The purity of iron oxide is >99%, the mass fraction of SiO2 is ≤0.01%, the mass fraction of chloride is ≤0.05%, and the average particle size is 0.90μm; the purity of strontium carbonate is >98.5%, and the average particle size is 1.5μm; the purity of calcium carbonate is >98.5%, and the average particle size is 3μm; the purity of lanthanum oxide is >99%, and the average particle size is 3μm; the mass fraction of cobalt in cobalt trioxide is >72%, and the average particle size is 2.5μm.

[0036] Step 2: Add water to the mixture and mix for 2 hours to obtain a primary slurry. After the primary slurry is dried, it is pre-sintered at a temperature of 1260°C for 2 hours to obtain a primary pre-burned material. The primary pre-burned material is put into a Raymond mill for primary grinding to obtain a primary pre-burned material powder with a particle size of 2 μm.

[0037] Step 3: Take 500g of the first pre-burned powder, add 2.5g of CaCO3, 1.8g of SiO2, 1g of Ca3(BO3)2 and 1.5g of sorbitol according to the percentage of the mass of the first pre-burned powder, and add the material (the sum of the first pre-burned powder, CaCO3, SiO2, Ca3(BO3)2 and sorbitol), ball (steel ball for ball milling) and water in a mass ratio of 1:8:1.5. The secondary slurry was ball-milled in a ball mill to obtain a secondary slurry, and the average particle size thereof was measured by WLP-216 to be 0.83 μm;

[0038] Step 4: Control the water content of the secondary slurry to 35%, and form the green body under the action of a magnetic field. The magnetizing magnetic field intensity during forming is 900 kA / m, and the density of the green body is 3.34 g / cm3 The diameter of the green body is The height is 15 mm, the moisture content of the green body is 13%, the green body is placed in a sintering kiln, heated to 900°C, then heated to 1200°C at a heating rate of 2°C / min, and kept warm for 90 minutes to obtain a sintered body. The demagnetization curve of the sintered body prepared in this embodiment is shown in Figure 1 , electron microscope image see Figure 2 .

[0039] Example 2

[0040] The difference from Example 1 is that the heating rate of 2°C / min in step 4 is adjusted to 1.8°C / min, and the other conditions and steps are the same as Example 1.

[0041] Example 3

[0042] The difference from Example 1 is that the heating rate of 2°C / min in step 4 is adjusted to 2.2°C / min, and the other conditions and steps are the same as Example 1.

[0043] Example 4

[0044] The difference from Example 1 is that the dosage of the composite auxiliary material is increased and the secondary ball milling process parameters are adjusted, and the other steps and conditions are the same as Example 1.

[0045] The specific steps are as follows:

[0046] Step 1: prepare raw materials according to weight proportions: 85 parts of iron oxide, 1 part of strontium carbonate, 5 parts of calcium carbonate, 5 parts of lanthanum oxide, and 2 parts of cobalt trioxide. Mix the raw materials evenly to obtain a mixture.

[0047] The purity of iron oxide is >99%, the mass fraction of SiO2 is ≤0.01%, the mass fraction of chloride is ≤0.05%, and the average particle size is 0.90μm; the purity of strontium carbonate is >98.5%, and the average particle size is 1.5μm; the purity of calcium carbonate is >98.5%, and the average particle size is 3μm; the purity of lanthanum oxide is >99%, and the average particle size is 3μm; the mass fraction of cobalt in cobalt trioxide is >72%, and the average particle size is 2.5μm.

[0048] Step 2: Add water to the mixture and mix for 2 hours to obtain a primary slurry. After the primary slurry is dried, it is pre-sintered at a temperature of 1250°C for 4 hours to obtain a primary pre-burned material. The primary pre-burned material is put into a Raymond mill for primary grinding to obtain a primary pre-burned material powder with a particle size of 3 μm.

[0049] Step 3: Take 500g of the first pre-burned powder, add 5g of CaCO3, 2.0g of SiO2, 0.5g of Ca3(BO3)2 and 2.5g of sorbitol according to the percentage of the mass of the first pre-burned powder, and add the material (the sum of the first pre-burned powder, CaCO3, SiO2, Ca3(BO3)2 and sorbitol), ball (steel ball for ball milling) and water in a mass ratio of 1:15:3. The secondary slurry was ball-milled in a ball mill to obtain a secondary slurry, and the average particle size thereof was measured by WLP-216 to be 0.80 μm;

[0050] Step 4: Control the water content of the secondary slurry to 35%, and form the green body under the action of a magnetic field. The magnetizing magnetic field intensity during forming is 900 kA / m, and the density of the green body is 3.35 g / cm 3 The diameter of the green body is The height is 15 mm, and the moisture content of the green body is 13%. The green body is placed in a sintering kiln, heated to 900°C, and then heated to 1200°C at a heating rate of 2°C / min, and kept warm for 90 minutes to obtain a sintered body.

[0051] Example 5

[0052] The difference from Example 1 is that the dosage of the composite auxiliary material is reduced and the secondary ball milling process parameters are adjusted. The other steps and conditions are the same as Example 1.

[0053] The specific steps are as follows:

[0054] Step 1: prepare raw materials according to weight proportions: 85 parts of iron oxide, 1 part of strontium carbonate, 5 parts of calcium carbonate, 5 parts of lanthanum oxide, and 2 parts of cobalt trioxide. Mix the raw materials evenly to obtain a mixture.

[0055] The purity of iron oxide is >99%, the mass fraction of SiO2 is ≤0.01%, the mass fraction of chloride is ≤0.05%, and the average particle size is 0.90μm; the purity of strontium carbonate is >98.5%, and the average particle size is 1.5μm; the purity of calcium carbonate is >98.5%, and the average particle size is 3μm; the purity of lanthanum oxide is >99%, and the average particle size is 3μm; the mass fraction of cobalt in cobalt trioxide is >72%, and the average particle size is 2.5μm.

[0056] Step 2: Add water to the mixture and mix for 2 hours to obtain a primary slurry. After the primary slurry is dried, it is pre-sintered at a temperature of 1350° C. and kept warm for 0.5 hours to obtain a primary pre-burned material. The primary pre-burned material is put into a Raymond mill for primary grinding to obtain a primary pre-burned material powder with a particle size of 1.6 μm.

[0057] Step 3: Take 500g of the first pre-burned powder, add 0.5g of CaCO3, 0.25g of SiO2, 2.5g of Ca3(BO3)2 and 0.5g of sorbitol according to the percentage of the mass of the first pre-burned powder, and add the material (the sum of the first pre-burned powder, CaCO3, SiO2, Ca3(BO3)2 and sorbitol), ball (steel ball for ball milling) and water in a mass ratio of 1:5:1. The secondary slurry was ball-milled in a ball mill to obtain a secondary slurry, and the average particle size thereof was measured by WLP-216 to be 0.89 μm;

[0058] Step 4: Control the water content of the secondary slurry to 35%, and form the green body under the action of a magnetic field. The magnetizing magnetic field intensity during forming is 900 kA / m, and the density of the green body is 3.35 g / cm 3 The diameter of the green body is The height is 15 mm, and the moisture content of the green body is 13%. The green body is placed in a sintering kiln, heated to 900°C, and then heated to 1200°C at a heating rate of 2°C / min, and kept warm for 90 minutes to obtain a sintered body.

[0059] Example 6

[0060] The difference from Example 1 is that the weight percentage of the raw materials in step 1 is different, and the heating rate of 2°C / min in step 4 is adjusted to 3°C / min, and the other conditions and steps are the same as Example 1. The weight percentages of the raw materials are as follows:

[0061] Iron oxide: 80 parts, strontium carbonate: 1 part, calcium carbonate: 5 parts, lanthanum oxide: 10 parts, cobalt trioxide: 2 parts.

[0062] Example 7

[0063] The difference from Example 1 is that the weight percentage of the raw materials in step 1 is different, and the heating rate of 2°C / min in step 4 is adjusted to 3°C / min, and the insulation time of 90min is adjusted to 60min. The other conditions and steps are the same as Example 1. The weight percentages of the raw materials are as follows:

[0064] Iron oxide: 86 parts, strontium carbonate: 1 part, calcium carbonate: 5 parts, lanthanum oxide: 10 parts, cobalt trioxide: 2 parts.

[0065] Example 8

[0066] The difference from Example 1 is that the weight percentage of the raw materials in step 1 is different, and the heating rate of 2°C / min in step 4 is adjusted to 1.5°C / min, and the other conditions and steps are the same as Example 1. The weight percentages of the raw materials are as follows:

[0067] Iron oxide: 85 parts, strontium carbonate: 1 part, calcium carbonate: 5 parts, lanthanum oxide: 4 parts, cobalt trioxide: 3 parts.

[0068] Example 9

[0069] The difference from Example 1 is that the weight percentage of the raw materials in step 1 is different, and the heating rate of 2°C / min in step 4 is adjusted to 1.5°C / min, and the insulation time of 90min is adjusted to 120min. Other conditions and steps are the same as Example 1. The weight percentages of the raw materials are as follows:

[0070] Iron oxide: 85 parts, strontium carbonate: 1 part, calcium carbonate: 5 parts, lanthanum oxide: 4 parts, cobalt trioxide: 3 parts.

[0071] Comparative Example 1

[0072] Compared with Example 1, the heating rate of step 4 in this comparative example was adjusted from 2°C / min to 1.3°C / min, and the other steps and conditions were the same as in Example 1.

[0073] Comparative Example 2

[0074] Compared with Example 1, the heating rate of step 4 in this comparative example was adjusted from 2°C / min to 3.2°C / min, and the other steps and conditions were the same as those in Example 1. The electron microscope image of the sintered body prepared in this comparative example is shown in Figure 3 .

[0075] The performance tests were conducted on the sintered bodies prepared in Examples 1 to 9 and Comparative Examples 1 to 2. The results are shown in Table 1.

[0076] The upper and lower surfaces of the sintered body were ground flat and finely ground with a 140-mesh grinding wheel, and then tested using the NIM-2000 permanent magnet material magnetic properties testing system manufactured by the Beijing Institute of Metrology.

[0077] Table 1

[0078]

[0079]

[0080] It can be seen from Table 1 that under the same raw material formula conditions in Examples 1 to 3, both increasing and decreasing the heating rate will affect the squareness of the ferrite. Under the formula and heating rate of Example 1, the ferrite prepared therefrom has high remanence and intrinsic coercivity, and the squareness reaches 0.952. The microstructure of the magnet in Example 1 is as follows: Figure 2As shown, SEM analysis of the cross-section of the magnet shows that its crystal structure is tightly arranged, the grain size is relatively uniform, the porosity in the magnet is 0.8%, and there are no abnormally growing grains (such as larger grains swallowing up surrounding small grains or pores and growing rapidly). In the raw material formulas of Example 6 and Example 7, the proportion of lanthanum is increased compared to Example 1. By increasing the heating rate and shortening the insulation time, it can be ensured that the prepared ferrite material has excellent comprehensive performance. Compared with Example 1, Example 8 and Example 9 increase the proportion of cobalt. In Example 9, the heating rate is increased and the insulation time is extended. The prepared ferrite material has excellent properties, among which the squareness reaches 0.971, and it has excellent anti-demagnetization ability. Compared with Example 1, the lower or higher heating rates in the comparative example result in a lower squareness value of the ferrite, and the magnetic material is easy to demagnetize. The electron microscope image of Comparative Example 2 is shown in Figure 3 As shown, the grain size deviation is large, the uniformity is poor, and there are abnormally grown grains.

[0081] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0082] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A production process for high-performance permanent ferrite, characterized in that: The steps include: Step 1, prepare raw materials according to weight proportions, iron oxide: 80-88 parts, strontium carbonate: 0.5-5 parts, calcium carbonate: 3-10 parts, lanthanum oxide: 4-10 parts, cobalt trioxide: 1-3 parts, and mix the raw materials evenly to obtain a mixture; Step 2: adding water to the mixture to obtain a primary slurry, drying the primary slurry, pre-sintering the primary slurry to obtain a primary pre-burned material, and grinding the primary slurry to obtain a primary pre-burned material powder; Step 3, adding composite auxiliary materials and water to the primary pre-burned powder for secondary ball milling to obtain secondary slurry; Step 4: The secondary slurry is subjected to magnetic field molding to obtain a green body, and the green body is placed in a sintering kiln. After heating to 900°C, the temperature is increased to 1200°C at a heating rate of 1.5-3°C / min, and kept warm for 60-120 minutes to obtain a sintered body, and the squareness of the sintered body is greater than 0.

92.

2. The production process of a high performance permanent ferrite according to claim 1, characterized in that: The purity of the iron oxide is greater than 99.0%, the purity of the strontium carbonate is greater than 98.5%, the purity of the calcium carbonate is greater than 98.5%, the purity of the lanthanum oxide is greater than 99%, and the mass fraction of cobalt in the cobalt trioxide is greater than 72%.

3. The production process of a high performance permanent ferrite according to claim 1, characterized in that: In step 2, the pre-sintering temperature is 1250-1350° C., and the holding time is 0.5-4 h.

4. The production process of a high performance permanent ferrite according to claim 1, characterized in that: In step 2, the equipment for the first grinding is a Raymond mill, and the particle size of the first pre-sintered powder is 1.5-3 μm.

5. The production process of a high performance permanent ferrite according to claim 1, characterized in that: In step 3, the mass ratio of the secondary ball milling is as follows: Ingredients: ball: water = 1: (5-15): (1-3).

6. The production process of a high performance permanent ferrite according to claim 1, characterized in that: Calculated as a percentage of the mass of the primary pre-burned powder, the composite auxiliary materials include: CaCO3: 0.1-1%, SiO2: 0.05-0.4%, dispersant: 0.1-0.5%, borate: 0.1-0.5%.

7. The production process of a high performance permanent ferrite according to claim 6, characterized in that: The dispersant is at least one of calcium gluconate and sorbitol.

8. The production process of a high performance permanent ferrite according to claim 6, characterized in that: The borate is calcium borate.

9. The production process of a high performance permanent ferrite according to claim 1, characterized in that: The particle size of the secondary slurry is 0.6-1.0 μm.

10. The production process of a high performance permanent ferrite according to claim 1, characterized in that: In step 4, the magnetic field strength of the magnetic field molding is 800-1000 kA / m; the density of the green body is 3.3-3.45 g / cm 3 .

Citation Information

Patent Citations

  • A high squareness permanent magnet strontium ferrite magnetic material and its preparation method

    CN114956801B

  • High-performance permanent magnetic ferrite and manufacturing method thereof

    CN104261811A

  • Rare earth-containing permanent magnetic ferrite and manufacturing method thereof

    CN104496457A

  • High performance strontium-calcium permanent magnetic ferrite magnet and preparation method thereof

    CN104692785A

  • Low-radial shrinkage ratio permanent magnetic ferrite magnet and preparation method thereof

    CN104692786A